Pengembangan Corporate Social Responsibility (CSR) Dalam Mewujudkan Community Development (Studi pada Program Kemitraan dan Bina Lingkungan (PKBL) PG Ngadirejo) - Mirza Gholami (Jurnal Administrasi Publik, 2014)
Abstract: Development Corporate Social Responsibility (CSR) in Creating Community Development (Study on the Partnership and Community Development Programs (PKBL) Ngadirejo Sugar Factory). As society increasingly critical and capable of social control over the business world. This calls for businesses to run their business more accountable. Therefore, PG Ngadirejo implement development CSR through PKBL with reference to community development perspective. This study used a qualitative approach and data analysis models Spradley. Development PKBL to achieve the community development partnership program through 1) the election of the target 2) the distribution of the allocation of funds 3) training 4) refund partnerships and 5) control, whereas community development, namely 1) ​​the election of the target 2) the distribution of the allocation of funds. The results of the research note, the partnership programs uses the approach of community for development because of the dominance of large companies are still so limited partner initiatives. While the community development programs using community with development approach because the public has a role in determining the types of social activities in accordance with their needs.   Keywords: Corporate Social Responsibility (CSR), Community Development, Partnership Programs and Community Development (PKBL)   Abstrak: Pengembangan Corporate Social Responsibility (CSR) dalam Mewujudkan Community Development (Studi pada Program Kemitraan dan Bina Lingkungan (PKBL) PG Ngadirejo). Seiring masyarakat semakin kritis dan mampu melakukan kontrol sosial terhadap dunia usaha. Hal ini menuntut kepada pelaku bisnis untuk menjalankan usahanya dengan semakin bertanggungjawab. Oleh karena itu, PG Ngadirejomelaksanakan pengembangan CSR melalui PKBL dengan mengacu pada perspektif community development. Penelitian ini menggunakan pendekatan kualitatif dan analisis data model Spradley. Pengembangan PKBL untuk mewujudkan community development yaitu program kemitraan melalui 1) proses penjaringan sasaran 2) penyaluran alokasi dana 3) pembinaan 4) pengembalian dana kemitraan dan 5) pengawasan sedangkan program bina lingkungan yaitu 1) proses penjaringan sasaran 2) penyaluran alokasi dana. Hasil penelitian diketahui, program kemitraan menggunakan pendekatan community for development karena dominasi perusahaan masih besar sehingga inisiatif mitra masih terbatas. Sedangkan dalam program bina lingkungan menggunakan pendekatan development with community karena masyarakat mempunyai peran dalam menentukan jenis kegiatan sosial sesuai dengan kebutuhannya.   Kata kunci: Corporate Social Responsibility (CSR), Community Development, Program Kemitraan dan Bina Lingkungan (PKBL)